Constructing the Teaching Guidebook for Children’s Chorus in Advanced Class at the Mastery Iris Blue Choir - Xinyi , Xie; Roongruang, Panya (Journal of Roi Kaensarn Academi, 2024)
The objectives of research were: (1) To study the techniques of children’s chorus teaching from key informants. (2) To construct the teaching guidebook for children in The Mastery Iris Blue Choir. (3) To experiment teaching children’s chorus singing skills by using the guidebook. (4) To evaluate the learning effectiveness by using the guidebook.This research methodology was mixed research method of qualitative and quantitative research. Gathering data by iteviewing three key informants. Research sample was 18 students in advanced class of Mastery Iris Blue Chior. The research tools included: interview form, teaching guidebook; formative tests and summative test and IOC form. Descriptive analysis was used to analyze the interview information from the three key informants and statistical analysis was used to analyze the scores of formative tests and summative test and the hypothesis set for formative test and summative test was at 4.00/4.00. The results of this research were: (1) The context of children’s choral education; it was imperative to take into account the distinctive cognitive framework of children. Designing appropriate pedagogical approaches to accommodate the physiological and psychological uniqueness of children during the process of learning to sing was crucial, emphasizing the continuity of knowledge in curriculum construction held paramount significance; (2) The teaching guidebook consisted of Introduction, How to use this teacher’s guide, Repertoire included 7 songs; (3) The guidebook was used for conducting the experimental group of students by using 15 lessons plans 90 minutes oer lesson; (4) The efficiency of teaching were evaluated from shown the rational score of formative and summative at 4.02 and 4.03, met with hypothesis ahich meants the Teaching Guidebook For Children’s Chorus In Advanced Class At The Mastery Iris Blue Choir was effective and being god for further use.